COMPARISON OF STEMMING AND SIMILARITY ALGORITHMS IN INDONESIAN TRANSLATED AL-QUR'AN TEXT SEARCH - Ika Oktavia Suzanti; Achmad Jauhari (Universitas Trunojoyo Madura, 2021)
The long history of information retrieval did not begin with Internet. Prior to widespread public daily use of search engines, in the 1960s information retrieval systems were discovered in commercial and intelligence applications. There are two stages in Information Retrieval in doing its main job which is to preprocessing text and to calculate similarity between term (word) and query (keyword) user searched for in a document. Stemming is final stage of pre-processing in an information retrieval system. The way stemming works is to remove affixes from a word, in form of prefixes, suffixes and insertions into form of basic word. Thus, in this paper we did compare search on information retrieval system without using stemming algorithm, using stemming Porter, Nazief & Adriani and Enhanced Confix Stripping with similarity method used is cosine similarity and dice similarity. Based on test results, text search ability on dice similarity is faster in stemming process with Porter Stemmer and ECS algorithms. While in Nazief & Adriani algorithm and without stemming, cosine similarity is faster than dice similarity.